Relationship between personality, misbehavior and academic achievement among freshmen in a university - Mahyuddin, Rahil; Yan, Li Siaw; Roslan, Samsilah; Ahmad Tarmizi, Rohani (The International Journal of the Humanities, 2009)
The national educational philosophy stated that the aim of education is to produce individuals not only knowledgeable but also possessing healthy personality. It is therefore the aim of this paper to determine the relationship between personality, misbehavior and academic achievement among freshmen at a local higher educational institution. The methodology employed in this study is descriptive correlation. The sample size is 372 first year students (180 boys and 192 girls) from 12 residential colleges of the university. The Eysenck Junior Personality Inventory was utilized to measure the personality aspect. By using the pearson correlation analysis, the results showed that there were a significant negative correlation (r=-0.191, p<0.01) between the extrovert scores and academic achievement and a significant positive correlations between neurotic scores and academic achievement. Findings also show that there was no relationship between misbehavior and academic achievement. In conclusion, the findings showed that individuals with good academic performance do not necessarily have good personality.